Effect of Milling Type on Formation of Carbon Nanostructures - Guler, Omer; Evin, Ertan (Taylor & Francis Inc, 2015)
In this study, graphite powder was exposed to two different stress types by using the same type of mill in order to understand the formation of different carbon nanostructures. Two types of milling modes were selected as shock-type and shear-type stresses during the milling processes. Both shock-type and shear-type stresses were applied to the graphite powder. Then, milled powders were annealed at high temperatures for different times. The structural changes in the obtained samples were determined by XRD diffraction, SEM, FE-SEM and HR-TEM examinations. New carbon nanostructures were synthesised.
Keywords: milling; carbon nanostructure; nanographene sheets